2001
DOI: 10.1021/jp0126053
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Reflection Absorption Spectroscopic and DFT Calculation Studies on the Adsorption Structures of Dimethyl Ether on Ag(110), Cu(110), and Their Atomic Oxygen-Reconstructed Surfaces

Abstract: Infrared spectra were measured at 80 K for dimethyl ether (CH3OCH3, DME) and dimethyl ether-d6 (CD3OCD3, DME-d6) with increasing amounts of exposures to metal substrates, Ag(110), Cu(110), and their atomic oxygen-reconstructed surfaces, p(2 × 1)O−Ag(110) and p(2 × 1)O−Cu(110). At relatively lower surface coverages, the IR spectra of DME on Ag(110) and Cu(110) in the 1500−800 cm-1 region give rise to IR bands mainly ascribable to A1 species, including symmetric COC stretching (νs(COC)) bands at 903 cm-1 on Ag(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The strong absorption at 2878 cm -1 is assigned to the m s (CH 3 ) fundamental enhanced by a Fermi resonance with a CH 3 bending mode [43]. To interpret the lower wavenumber region, it is instructive to compare our results with those obtained by Kasahara et al by RAIRS of DME adsorbed on Cu(111), Ag(111), Cu(110) and Ag(110) [30,31]. Based upon their assignments, the peak at 919 cm -1 is assigned to t s (COC) and the peak at 1452 cm -1 is assigned to d a (CH 3 ).…”
Section: Diethyl and Dimethyl Ether Adsorbed On Ru(0001)supporting
confidence: 63%
See 1 more Smart Citation
“…The strong absorption at 2878 cm -1 is assigned to the m s (CH 3 ) fundamental enhanced by a Fermi resonance with a CH 3 bending mode [43]. To interpret the lower wavenumber region, it is instructive to compare our results with those obtained by Kasahara et al by RAIRS of DME adsorbed on Cu(111), Ag(111), Cu(110) and Ag(110) [30,31]. Based upon their assignments, the peak at 919 cm -1 is assigned to t s (COC) and the peak at 1452 cm -1 is assigned to d a (CH 3 ).…”
Section: Diethyl and Dimethyl Ether Adsorbed On Ru(0001)supporting
confidence: 63%
“…Further explanation on these controversial results stated that probably the different experimental conditions and preparation of the high surface area catalysts were responsible for the different results obtained. [26] Alkyl ethers have also been of interest due to their role as lubricants leading to studies to elucidate the reactivity of alkyl and perfluoro-alkyl ethers on metals [27][28][29][30][31] and on oxides [13,14,[32][33][34][35][36][37][38][39]. It is interesting to note that several of these studies showed reaction of the ethers adsorbed on the oxides (Al 2 O 3 , SiO 2 , TiO 2 and ZrO 2 ) to form alkoxides, potentially due to the presence of hydroxyls and also further conversion of these alkoxides to carboxylates.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from Figure 8B, the orientation of MEE in the G form on Cu(110) is favorable for the oxygen atom to coordinate to a bridge site of the surface metal atoms through the two lone pair electrons as in the case of DME on Cu(110). 7 On the other hand, MEE in the T form cannot take on the bridge coordination site on Ag(110) because of the steric repulsion between the CH 3 (-CH 2 ) group and the surface. Presumably, one of the lone pair electrons of the oxygen atom participates in a coordination interaction, as shown in Figure 8A.…”
Section: Discussionmentioning
confidence: 99%
“…As for the factor i, it has been known that the T form of MEE in the gaseous state is more stable than the G form with the enthalpy difference of 5.65 kJ/ mol. 3 The results of the IRA study on dimethyl ether (DME) adsorbed on Cu(110) and Ag(110) 7 suggests that the intrinsic coordination interaction between the oxygen atom of MEE and the surface metals on Cu(110) is stronger than that on Ag(110). Presumably, this is one of the main reasons for the fact that MEE takes the G form on Cu(110), even if it is energetically unfavorable compared to the T form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation